Triplets electrically turn on insulating lanthanide-doped nanoparticles - Zhongzheng Yu; Yunzhou Deng; Junzhi Ye; Lars van Turnhout; Tianjun Liu; Alasdair Tew; Rakesh Arul; Simon Dowland; Yuqi Sun; Xinjuan Li; Linjie Dai; Yang Lu; et al. (Nature, 2025)
Abstract Insulating nanomaterials have large energy gaps and are only electrically accessible under extreme conditions, such as high-intensity radiation and high temperature, pressure or voltage 1,2 . Lanthanide-doped insulating nanoparticles (LnNPs) are widely studied owing to their exceptional luminescence properties, including bright, narrow-linewidth, non-blinking and non-bleaching emission in the second near-infrared (NIR-II) range 3,4 . However, it has not been possible to electrically generate excited states in these insulating nanomaterials under low biases and, therefore, not possible to fabricate optoelectronic devices from these systems. Here we report an electrical excitation pathway to obtain emission from LnNPs. By forming LnNP@organic molecule nanohybrids, in which the recombination of electrically injected charges on the organic molecule is followed by efficient triplet energy transfer (TET) to the LnNP, it is possible to turn on LnNPs under a low operating bias. We demonstrate this excitation pathway in light-emitting diodes (LEDs), with low turn-on voltages of about 5 V, very narrow electroluminescence (EL) spectra and a peak external quantum efficiency (EQE) greater than 0.6% in the NIR-II window 5 . Our LnNP-based LEDs (LnLEDs) also allow for widely tunable EL properties, by changing the type and concentration of lanthanide dopants. These results open up a new field of hybrid optoelectronic devices and provide new opportunities for the electrically driven excitation sources based on lanthanide nanomaterials for biomedical and optoelectronic applications.